IMPROVING COGNITIVE LEARNING OUTCOMES OF SCIENCE LESSONS THROUGH PROBLEM BASED LEARNING MODELS ASSISTED BY PUZZLES - Septi Nur Chayani; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
This study aims to determine the increase in cognitive learning outcomes of fifth grade students at SDN Sumobito 01 in science learning after learning classroom action. The research method used is descriptive quantitative method. The instruments used in this study were observation sheets and interview sheets as well as pretest and posttest question sheets. The assessment indicator set in this study is that student learning outcomes will be completed if they reach the target of 70%. So this research will be successful if the learning outcomes of students reach 70%. The results obtained are the learning outcomes of fifth grade students have increased by 11.6% from the first cycle. Where the learning mastery results in the first cycle are 65.3% and then increased in the second cycle with 76.9% mastery results. With an increase in mastery from cycle I to cycle II, it can be found that the use of Problem Based Learning (PBL) learning models using puzzle-based media in science subjects learning materials in humans can improve learning outcomes for fifth grade students at SDN Sumobito 01.